AINTEGUMENTA and AINTEGUMENTA-LIKE6 directly regulate floral homeotic, growth, and vascular development genes in young Arabidopsis flowers. (20th May 2021) - Krizek, Beth A; Bantle, Alexis T; Heflin, Jorman M; Han, Han; Freese, Nowlan H; Loraine, Ann E
Abstract : Arabidopsis ANT and AIL6 directly regulate genes involved in different aspects of early flower development including genes that specify floral organ identity and those that regulate growth and vascular development. Abstract: Arabidopsis flower primordia give rise to organ primordia in stereotypical positions within four concentric whorls. Floral organ primordia in each whorl undergo distinct developmental programs to become one of four organ types (sepals, petals, stamens, and carpels). The Arabidopsis transcription factors AINTEGUMENTA (ANT) and AINTEGUMENTA-LIKE6 (AIL6) are required for correct positioning of floral organ initiation, contribute to the specification of floral organ identity, and regulate the growth and morphogenesis of developing floral organs. To gain insight into the molecular mechanisms by which ANT and AIL6 contribute to floral organogenesis, we identified the genome-wide binding sites of both ANT and AIL6 in stage 3 flower primordia, the developmental stage at which sepal primordia become visible and class B and C floral homeotic genes are first expressed. AIL6 binds to a subset of ANT sites, suggesting that AIL6 regulates some but not all of the same target genes as ANT. ANT- and AIL6-binding sites are associated with genes involved in many biological processes related to meristem and flower organ development. Comparison of genes associated with both ANT and AIL6 ChIP-Seq peaks and those differentially expressed after perturbation of ANT and/or AIL6 activity identified likely direct targets of ANT and AIL6 regulation. These include class B and C floral homeotic genes, growth regulatory genes, and genes involved in vascular development.